(untitled) (Asian Journal of Pharmaceutics (AJP), 2023)
Introduction and Aim: Lactic acid bacteria (LAB) with remarkable functional properties have been isolated from different fermented food products. Ngari and soibum are fermented fish and fermented bamboo shoot products produced in Manipur, India. The present study was conducted to isolate potential probiotic strains from ngari and soibum also to evaluate their antioxidant and anti-inflammatory activities. Materials and Methods: LAB strains were isolated from ngari and soibum samples, characterized, and evaluated for probiotic properties including acid and bile tolerance, antimicrobial activity, antibiotic susceptibility, and hemolytic activity. The strains were identified by 16S rRNA gene sequencing. Two strains with the best probiotic potential were selected and evaluated for antioxidant activity by 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2-Azino-bis-(3-ethylbenzothiazoline-6- sulfonic acid) diammonium salt (ABTS) radical scavenging assays and anti-inflammatory activity by real-time polymerase chain reaction. Results: The isolates were capable of surviving in an environment with low pH (pH 2) and with bile salts (0.3% oxgall). The cell-free supernatant of the isolates showed high antibacterial activity against the tested pathogens. The isolates were sensitive to most of the test antibiotics and none of the isolates showed hemolytic activity. By 16S rRNA gene sequencing, the isolates were identified as Lactiplantibacillus plantarum (five strains) and Enterococcus faecium (one strain). L. plantarum strains NG28 and SB15 exhibited high antioxidative capacity in terms of DPPH and ABTS radical scavenging assays. These two strains were also capable of reducing the production of nitric oxide as well as the expression of nitric oxide synthase and cyclooxygenase-2 as well as pro-inflammatory cytokines, such as tumor necrosis factor-α, interleukin (IL)-1β, and IL-6 in lipopolysaccharide-induced RAW 264.7 cells. Conclusion: The selected LAB strains possess the potential probiotic and beneficial functional properties. Hence, they could be used in functional foods and pharmaceutical applications.